Effects of Juglans regia Root Bark Extract on Platelet Aggregation, Bleeding Time, and Plasmatic Coagulation: In Vitro and Ex Vivo Experiments. (14th August 2018) - Amirou, A.; Bnouham, M.; Legssyer, A.; Ziyyat, A.; Aziz, M.; Berrabah, M.; Mekhfi, H.
Abstract : Platelets have an important role in thrombosis and haemostasis. Hyperactivity of the platelets has been associated with thromboembolic diseases and represents the main cause of complications of cardiovascular diseases. Crude aqueous extract (CAE) of Juglans regia root bark was evaluated for bleeding time, antiaggregant activity by using agonists, thrombin, ADP, collagen, or arachidonic acid ( in vitro and ex vivo ), and anticoagulant activity by measuring the clotting parameters: activated partial thromboplastin time, prothrombin time, thrombin time, and fibrinogen dosage ( in vitro and ex vivo ). The result of this study reported that the strongest antiaggregant effect of CAE in vitro was observed on the ADP-induced aggregation with inhibitions up to 90 %, while, in ex vivo experiments, the inhibition (more than 80 %) was observed with all agonists. Anticoagulant effect of CAE significantly prolonged the TT and decreased the fibrinogen level in vitro and ex vivo without interfering with APTT and PT. The bleeding time in mice and rats was significantly increased by CAE. The antiplatelet and anticoagulant effect observed in this study suggest that Juglans regia could have antithrombotic and/or thrombolytic activities and provide an alternative therapy against thrombotic complications related to cardiovascular diseases.